Serum ferritin concentration in early pregnancy and risk of subsequent development of gestational diabetes: A prospective study - Sedigheh Soheilykhah; Mahdieh Mojibian; Maryam Jannati Moghadam (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Elevated serum ferritin concentration is associated with insulinresistance and diabetes. Recently it has also been described in gestational diabetesmellitus (GDM). Objective: A prospective study was done to determine whether there was arelationship between serum ferritin concentration in early pregnancy and the risk ofGDM. Materials and Methods: A study was performed on 1,384 pregnant women withgestational age of 12-16 weeks. A blood sample was obtained for measurement offerritin in the first trimester. Diagnosis of GDM was done by 75 gr oral glucosetolerance test between 24-28 wk. Results: Women who developed GDM had a higher concentration of serum ferritinthan women who did not develop GDM (p=0.01). A ferritin concentration of 45ng/ml was calculated to be the 75th percentile for healthy pregnant women.Considering this level 32% in the GDM group and 25.2%of normal subjectsexhibited high ferritin levels (p=0.01). The risk of GDM with these high levels offerritin was 1.4-fold higher than that for subjects with lower concentrations. The Odds Ratio was 1.4 (95% CI= 1-1.87) (p=0.01). After adjusted for age Odds Ratiowas 1.38 (95% CI=1.02-1.86) (p=0.03) and after adjustment for pre-pregnancy BodyMass index, the adjusted odds ratio was 1.31 (CI= 0.96-1.79) (p=0.08). Aftermultivariable adjustment (age and body mass index), the adjusted odds ratio was 1.3(0.95-1.8) (p=0.09). Conclusion: High serum ferritin can be regarded as a significant risk factor for thedevelopment of gestational diabetes